Coping with drought risk in agriculture and water supply systems : drought management and policy development in the Mediterranean - Iglesias, Ana. (Springer, 2017)
Coping with Drought Risk in Agriculture and Water Supply Systems addresses the growing issue of drought preparedness planning, monitoring, and mitigation which has worldwide application. The book collates considerable information from diverse disciplines. The information is presented to appeal to a broad scientific and policy audience seeking to develop proactive drought management plans effective for decreasing social vulnerability.